RESEARCH ON GREENHOUSE APPLICATION IN THE TROPICS - Herry Suhardiyanto; Yayu Romdhonah (PERTETA, 2007)
ABSTRACTStudies on greenhouse technology for tropical conditions show significant progress in the last decade. Several concepts of adapted greenhouse structure heve been proposed by scientists in ordor to provide optimum environment for the growing plants inside, This paper reviews on some studies concentrated on Improving the performance of greenhouse structure for tropical conditions. It presents some information on the design. material selection and the construction of several proposed greenhouses. It is hoped to give helpful information for future research as well as be implemented in commercial greenhouses In the tropics Keywords: greenhouse. natural ventilation. structural design, tropics. Diterima: 17 September 2007; Disetujui: 28 Oktober 2007